2020
DOI: 10.1002/ajmg.a.61846
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice variant expands the LAMC3‐associated cortical phenotype to frontal only polymicrogyria and adult‐onset epilepsy

Abstract: Bi-allelic loss-of-function variants in LAMC3, encoding extracellular matrix protein laminin gamma 3, represent a rare cause of occipital polymicrogyria with epilepsy, developmental delay and cognitive impairment. So far, only five families have been reported. We now identified a novel, homozygous splice variant in LAMC3 in an individual with an unusual manifestation of cortical malformation. She presented with polymicrogyria in the frontal but not the occipital lobes, with adult-onset seizures and normal psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Until now, 7 unrelated families worldwide have been reported to exhibit cortical malformations due to LAMC3 variants. All these patients with LAMC3 variants exhibited cortical malformations involving the occipital lobe, except for the patient reported by Qian et al, 4 while Kasper et al 3 reported a patient with cortical malformation predominantly in the frontal lobe. In addition, a patient reported by Zamboni et al also exhibited cortical malformation in the frontal, parietal, and temporal lobes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Until now, 7 unrelated families worldwide have been reported to exhibit cortical malformations due to LAMC3 variants. All these patients with LAMC3 variants exhibited cortical malformations involving the occipital lobe, except for the patient reported by Qian et al, 4 while Kasper et al 3 reported a patient with cortical malformation predominantly in the frontal lobe. In addition, a patient reported by Zamboni et al also exhibited cortical malformation in the frontal, parietal, and temporal lobes.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical symptoms may arise later during infancy or even adulthood in milder cases. [1][2][3][4][5] Seizures, developmental delay, impaired visual function, and cognitive delays can also be observed in affected individuals. Variants in actin-associated or microtubule-associated genes have been associated with cortical malformation.…”
mentioning
confidence: 99%
“…In nearly all reported cases a frameshift or non-sense LAMC3 variant was detected, except for missense variants in compound heterozygosity in two patients (Barak et al, 2011;De Angelis et al, 2021). Differently from the early literature reporting that only occipital lobes were involved in the cortical malformation process (Barak et al, 2011;Afawi et al, 2016), more recent studies (Zambonin et al, 2018;Kasper et al, 2020;De Angelis et al, 2021;Qian et al, 2021) and the structural analysis of previously reported individuals (Urgen et al, 2019) have demonstrated that LAMC3 variants can cause structural cerebral anomalies going beyond the occipital lobes, which sometimes can even be spared (Kasper et al, 2020;Qian et al, 2021). Awafi et al identified a consanguineous Arab family in which, out of 14 siblings, all the affected children (n = 6) and one unaffected sibling shared the same LAMC3 homozygous variant; all the affected family members had epilepsy and ID, but their computed tomography scans were unremarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Recessive LAMC3 gene variants cause occipital cortical malformations (Barak et al, 2011), such as pachygyria or polymicrogyria. However, the spectrum of LAMC3-associated cortical malformations has progressively expanded over time, showing that other cortical areas could be affected and that occipital lobes could even be spared in some cases (Zambonin et al, 2018;Kasper et al, 2020;De Angelis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%